Seismic Retrofit of Existing Masonry Buildings through Inter-story Isolation System: A Case Study and General Design Criteria. Issue 4 (12th March 2022) - Faiella, Diana; Calderoni, Bruno; Mele, Elena
ABSTRACT: This paper investigates the potentials of inter-story isolation systems (IIS) for retrofitting irregular masonry buildings by means of an isolated vertical addition realised on the roof of the existing structure. By assuming a case study, a wide parametric analysis is firstly carried out on lumped-masses model for identifying the dynamic properties of the isolated superstructure that minimizes the global seismic response. Hence, a 3D FE model is adopted for the detailed design and analysis of the IIS structure, with different solutions, in order to regularize the global seismic response of the IIS complex. Finally, some general design criteria are suggested.